The Controling of Iron (Fe) Toxicity with Humic Matter from Rice Straw Compost and Water Management to Increasing Productivity Established Rice Field at Sitiung, West Sumatra - Herviyanti Herviyanti; T. Budi Prasetyo; F. AHMAD; M. Harianti (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2011)
This experiment is held to sudy the potency of humic matter extracted from composted rice straw, combined with the various water management systems, in controlling the iron (Fe) toxicity in new-established rice field. The objective of this research is to get break through technology of controlling the iron toxicity in new-established rice field using the the humic substances and water management systems in order to get the optimum yield. This experiment uses a split-plot design with main plots are having three water management systems : continuous flooding; one week flooding and two weeks in field capacity; and two weeks flooding and two weeks in field capacity and sub-plots are having three levels of humic matter application : no humic matter; with 150 ppm humic matter = 300 kg ha-1; and with 300 ppm humic matter = 600 kg ha-1. The result shows that the application of humic matter extracted from composted rice straw decreases the Fe2+ concentration to be 135.67 ppm and 222.33 ppm in all three water management systems after eight weeks flooding. The best treatment combination is the plot with 600 kg ha-1 humic matter and 1 week flooding-2 weeks in field capacity, for it decreases Fe2+ concentration from 694 ppm down to 310 ppm, and the dry weight of grain is 1,819.7 g plot-1 (1 plot = 6 m2) or raising 770.8 g plot-1 compared with those plots with no humic matter and with continuous flooding.